Risk factors for incident HSV-2 infections among a prospective cohort of HIV-1-discordant couples in China. (2nd July 2015) - Ding, Yingying; Wu, Zunyou; Duan, Song; Rou, Keming; Yang, Yuecheng; Wang, Jibao; Gao, Meiyang; Ye, Runhua; Detels, Roger; He, Na
Abstract : Objectives: Identification of risk factors is essential for developing herpes simplex virus type 2 (HSV-2) prevention interventions that could also reduce HIV-1 transmission, particularly among HIV-1-discordant couples. Methods: A prospective cohort study was conducted among HIV-1-discordant couples from June 2009 to March 2011 in Yunnan province, China. 413 HIV-1-infected partners and 517 HIV-1-uninfected partners who were HSV-2 seronegative or equivocal at enrolment and who had a study partner completing the baseline survey and HSV-2 testing were included in the analysis. Results: HSV-2 incidence was 2.9 per 100 person-years (PY) for HIV-1-infected partners and 4.5 per 100 PY for HIV-1-uninfected partners. At least 36% of incident HSV-2 infections were from outside sexual partner. Among HIV-1-infected partners, multivariate analysis indicated that HSV-2 incidence was significantly higher among those with baseline equivocal HSV-2 result, having an initially HSV-2 seropositive or equivocal partner, reporting no sex with study partner and initiating antiretroviral therapy (ART) during follow-up. Among HIV-1-uninfected partners, multivariate analysis indicated that HSV-2 incidence was significantly higher among those having an initially HSV-2 seropositive partner and reporting sex with study partner ≥5 times/month, but was lower among those having a partner with baseline CD4 + count ≥350 cells/μL. Conclusions: Our findings underscore the importance of developing prevention and intervention programmes to reduce HSV-2 transmission among this population. The relationship between ART initiation and HSV-2 seroconversion requires further investigation.